Philosophical Reflections on Antiquity Historical Change. - Fairfield, Paul (Lexington Books, 2020)
This book examines the transitional periods of archaic Greece and late antiquity, the ostensible birth and death of the ancient west. The author argues that an interpretation of the social, political, and intellectual history of these important turning points brings to light some philosophical understanding of the dynamics of change itself.